2010
DOI: 10.1007/s10689-010-9338-5
|View full text |Cite
|
Sign up to set email alerts
|

Novel germline mutations in BRCA2 gene among breast and breast-ovarian cancer families from Poland

Abstract: Identification of mutations in the BRCA2 gene and estimation of their clinical consequences for women and men treated in the Maria Sklodowska-Curie Memorial Cancer Center Warsaw, Poland in the years 1998-2008. The probands (97 women and 8 men) had a family history of breast and ovarian cancer (median age 46). The presence of molecular changes was examined in DNA isolated from peripheral blood lymphocytes. Germline mutations in 27 exons of the BRCA2 gene were screened by 'touchdown' PCR amplification, DHPLC and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Two patients carried the likely pathogenic BRCA2 mutation c.9371A > T. This substitution is located in an evolutionarily conserved region of the BRCA2 gene and is predicted to adversely affect ssDNA interaction and the structural integrity of the C-terminal domain of the protein [ 40 , 41 ]. This variant has previously been reported in 11 unrelated patients from Poland (Table 3 ) [ 25 , 34 , 36 , 42 ]. Kluska et al recently identified the variant in six patients and proposed its inclusion in the list of Polish founder mutations [ 25 ].…”
Section: Discussionmentioning
confidence: 66%
“…Two patients carried the likely pathogenic BRCA2 mutation c.9371A > T. This substitution is located in an evolutionarily conserved region of the BRCA2 gene and is predicted to adversely affect ssDNA interaction and the structural integrity of the C-terminal domain of the protein [ 40 , 41 ]. This variant has previously been reported in 11 unrelated patients from Poland (Table 3 ) [ 25 , 34 , 36 , 42 ]. Kluska et al recently identified the variant in six patients and proposed its inclusion in the list of Polish founder mutations [ 25 ].…”
Section: Discussionmentioning
confidence: 66%
“…The incidence of SNVs and indels within 167 amplicons covering the BRCA1 and BRCA2 exons was tested using the Ion Torrent PGM sequencer in 31 (a training set) and 512 women with breast cancer or ovarian cancer newly diagnosed before the age of 50 years who were positive and negative for BRCA1/2 mutations, respectively, as determined by targeted genotyping. The genotyping comprised 11 mutations in BRCA1 , namely c.66_67delAG, C61R, c.3700_3704del5, c.3756delGTCT, c.3777delT, c.4035delA, c.4041delAG, c.4065delTCAA, c.5263delC, R1738E and R1751X, and nine mutations in BRCA2 , namely E394X, c.5239insT, c.5946delT, c.5964delAT, c.6447delTA, c.7910del5, c.8924delT, R3128X and c.9402delT [ 7 , 30 ]. Of the 512 women, 317 had familial breast and/or ovarian cancer, and 195 had only early onset cancer and/or contralateral breast and ovarian cancers; the median age of women with breast cancer at diagnosis was 43 years.…”
Section: Resultsmentioning
confidence: 99%
“… *Eleven BRCA1 mutations (c.66_67delAG, C61R, c.3700_3704del5, c.3756delGTCT, c.3777delT, c.4035delA, c.4041delAG, c.4065delTCAA, c.5263delC, R1738E and R1751X) and nine BRCA2 mutations (E394X, c.5239insT, c.5946delT, c.5964delAT, c.6447delTA, c.7910del5, c.8924delT, R3128X and c.9402delT) [ 7 , 30 ]. #family tree is depicted in Additional file 2 .…”
Section: Discussionmentioning
confidence: 99%